ANALISA STRATEGI DALAM PEMASARAN (Studi Kasus pada Mie Gacoan di Karangtengah Kota Blitar) - Indria Guntarayana; Krisma Putri; Ratih Y Chuly (Universitas Islam Balitar, 2018)
The marketing strategy is an important thing for the sustainability of a business, therefore this research was conducted with the aim to find out the marketing strategy of the gacoan noodle culinary business in Karangtengah, Blitar City. Due to the many existing noodle restaurants, the competition in this business is getting tougher. Therefore, it is important for noodle restaurant business people to be able to provide satisfaction for consumers through quality products and services in order to compete in the noodle restaurant business. This study uses a qualitative method, for the data collection method used in this study is to conduct direct observation techniques or in-depth observations and interviews. The analysis tool is to use SWOT Analysis and SWOT Analysis Deming Cycle. Based on the analysis and discussion it can be concluded and described that the marketing strategy of Gacoan Noodles can be said to be good, Gacoan Noodles sells its products both Offline and Online.